How to avoid a climate disaster [large type] : the solutions we have and the breakthroughs we need - Gates, Bill, 1955- (Random House Large Print, 2021)
"Bill Gates shares what he's learned in more than a decade of studying climate change and investing in innovations to address the problems, and sets out a vision for how the world can build the tools it needs to get to zero greenhouse gas emissions. Bill Gates explains why he cares so deeply about climate change and what makes him optimistic that the world can avoid the most dire effects of the climate crisis. Gates says, "We can work on a local, national, and global level to build the technologies, businesses, and industries to avoid the worst impacts of climate change." His interest in climate change is a natural outgrowth of the efforts by his foundation to reduce poverty and disease. Climate change, according to Gates, will have the biggest impact on the people who have done the least to cause it. As a technologist, he has seen firsthand how innovation can change the world. By investing in research, inventing new technologies, and by deploying them quickly at large scale, Gates believes climate change can be addressed in meaningful ways. According to Gates, "to prevent the worst effects of climate change, we have to get to net-zero emissions of greenhouse gases. This problem is urgent, and the debate is complex, but I believe we can come together to invent new carbon-zero technologies, deploy the ones we have, and ultimately avoid a climate catastrophe""--